Trilobolide and related sesquiterpene lactones from Laser trilobum possessing immunobiological properties - Harmatha, Juraj; Buděšínský, Miloš; Vokáč, Karel; Kostecká, Petra; Kmoníčková, Eva; Zídek, Zdeněk (Fitoterapia, 2013)
Three new and five known sesquiterpene lactones were isolated from the roots of Laser trilobum (L.) Borkh. Chemical identity of the known compounds and structural analysis of the new ones were determined by HR MS and NMR spectroscopy. The two new sesquiterpene lactones: 2-acetoxytrilobolide and 2-hydroxy-10-deacetyltrilobolide belong to the guaianolide type, and the third one, eudeslaserolide, to the biogenetically related eudesmanolide type. Both types, together with their biogenetic precursor of germacranolide type (laserolide) are present in L. trilobum, as well as in the related Laserpitium species. Purposefully selected set of these native sesquiterpene lactones was tested for specific immunobiological properties. The obtained results demonstrate that trilobolide and its acetoxy analog are strong activators of cytokine secretion. On the contrary, the other L. trilobum and Laserpitium siler constituents are only very mild activators, or even inhibitors of the cytokine and nitric oxide production.
Keywords: Nitric Oxide; Rats, Wistar; rostlinné extrakty; Butyrates; molekulární struktura; Molecular Structure; cytokiny; Plant Roots; butyráty; furany; oxid dusnatý; potkani Wistar; Sesquiterpenes; Sesquiterpene; kořeny rostlin; seskviterpeny; krysa rodu Rattus; Adjuvants, Immunologic; Animals; Plant Extracts; Trilobolide; ženské pohlaví; Thapsigargin; adjuvancia imunologická; zvířata; Cytokine; laktony; Lactones; Rats; Nitric oxide; Cytokines; Apiaceae; Female; Furans; Laser trilobum